Pelatihan Entrepeunership Berbasis Digital pada Santri Pondok Pesantren Al Ittihad Darunnajah Trenggalek - Tio Ari Laksono; Halimatus Sa’dyah; Muhammad Khoiri; Purwanto Purwanto (Jurnal Pelayanan Masyarakat, 2025)
This community service activity aims to enhance digital literacy and digital entrepreneurship skills among teachers and students (santri) at Pondok Pesantren Al Ittihad Darunnajah. The main issue faced by the partner institution is the low level of understanding in utilizing digital technology as a medium for business development. Using a Participatory Action Research (PAR) approach, the program was carried out through stages of observation, planning, training, and evaluation, employing lectures, discussions, and hands-on practice with digital platforms. The results show a significant improvement in participants’ understanding of digital entrepreneurship, online marketing, and technology-based business management. Participants were able to apply basic skills such as creating e-commerce accounts, promoting products, and managing simple financial records. Overall, this program successfully fostered student independence and economic empowerment through the utilization of digital technology and strengthened the role of the pesantren as a center for modern entrepreneurial development.